2012
DOI: 10.1016/j.micpath.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cronobacter spp. (previously Enterobacter sakazakii) invade and translocate across both cultured human intestinal epithelial cells and human brain microvascular endothelial cells

Abstract: a b s t r a c tThe mechanism of Cronobacter pathogenesis in neonatal meningitis and potential virulence factors (aside from host cell invasion ability) remain largely unknown. To ascertain whether Cronobacter can invade and transcytose across intestinal epithelial cells, enter into the blood stream and then transcytose across the blood-brain-barrier, we have utilized human intestinal INT407 and Caco-2 cells and brain microvascular endothelial cell (HBMEC) monolayers on Transwell filters as experimental model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 43 publications
2
37
0
3
Order By: Relevance
“…Nonetheless, not all Cronobacter spp. were positive for OmpA using the primers described by Nair & Venkitanarayanan (2007), as reported by Jaradat et al (2009) and Giri et al (2012).…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…Nonetheless, not all Cronobacter spp. were positive for OmpA using the primers described by Nair & Venkitanarayanan (2007), as reported by Jaradat et al (2009) and Giri et al (2012).…”
mentioning
confidence: 64%
“…is dose-dependent, but not due to a property of a particular bacterial species as a whole, rather a characteristic(s) of certain strains, which may be innocuous in a full-term, yet pathogenic in a pre-term infant (Hamby et al, 2011;Cetinkaya et al, 2013). In vitro models of infection also suggest that the organism may also gain entrance into the systemic circulation through transcytosis of the GIT epithelium (Giri et al, 2012).…”
Section: Necmentioning
confidence: 99%
See 2 more Smart Citations
“…13 A more recent study observed significant levels of transcytosis across a tight monolayer of HBMEC and included electron-microscopic analysis demonstrating the presence of Cronobacter within host vacuoles of HBMEC, in addition to being trancytosed at the basolateral surface. 88 While significant strain variation was noted, this study further contributes to our understanding of how this gastrointestinal pathogen penetrates the blood brain barrier (BBB) and ultimately causes meningitis. The previously mentioned OmpA protein, which plays a role in attachment of C. sakazakii to the gastrointestinal tract, has also been implicated in the invasion of HBMEC.…”
mentioning
confidence: 81%